THE EFFECTIVENESS OF CHEMISTRY MEDIA LEARNING BASED ON AUTOPLAY MEDIA STUDIO 8.0 TO IMPROVE STUDENTS’ COLLABORATIVE CHARACTER IN ACID-BASE MATERIAL - Irfandi (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2020)
This study aimed at discovering the effectiveness of auto play media studio 8.0 based chemistry media learning to improve the students’ collaborative character in acid-base material in SMAN 6 Pekanbaru. A Purposive sample was used as a method of study using an analysis of Independent Sample t-Test. The obtained data were the observation results data during learning processes. The results of the study indicated that the use of auto play media studio 8.0 based chemistry media learning was effective and significantly improved the students’ collaborative character, in which the significance value of Independent Sample t Test was 0,000. Based on the average results of collaborative character before and after the use of chemistry media learning based on auto play media studio 8.0 increased by 71%.